Sodobni mediji v luči pouka likovne vzgoje, ki temelji na konstruktivistični teoriji - Herzog, Jerneja (Revija za elementarno izobraževanje, 2008)
Modern Media in the Light of Fine Art as a School Subject Based on the Constructive Theory. The introduction of the article presents a terminological definition of media in general and a terminological definition of media within Fine Art as a school subject. It also presents the influence of media on Fine Art as a school subject. Furthermore, the author discusses the uses of modern media in Fine Art, selecting media and the suitability of individual media according to set artistic tasks. The main part of the article presents the constructive theory of teaching with its characteristics and applies them to teaching Fine Art, where the author sees connections and similarities. The remainder of the article presents the author's thesis, which is about the suitability of Fine Art as a school subject based on the constructive theory with use of modern media and multimedia.